1979
DOI: 10.1038/bjc.1979.112
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental arginine depletion by macrophages in vivo

Abstract: Summary.-Since the tumour-selective cytotoxic activity of activated macrophages in vitro can be attributed to depletion of the culture medium of L-arginine by macrophage arginase, a series of experiments was designed to determine whether such a mechanism could operate in vivo.Extracellular fluid obtained from Gullino chambers within established tumours contained high levels of arginase, no detectable arginine and high levels of ornithine. When tumours were disaggregated into single-cell suspensions, arginase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…Sufficient quantities of arginase can limit the availability of arginine for NO synthesis by intact cells. For example, in wounds [222][223][224] and macrophage cultures [225,226], the extracellular fluid becomes almost completely depleted of arginine, whereas ornithine increases, indicative of high arginase activity. More recently, inhibition of arginase in LPS-treated rodent macrophages was shown to result in enhanced conversion of arginine into citrulline, indicating that arginase and iNOS can compete for arginine [227,228].…”
Section: Arginase and No Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient quantities of arginase can limit the availability of arginine for NO synthesis by intact cells. For example, in wounds [222][223][224] and macrophage cultures [225,226], the extracellular fluid becomes almost completely depleted of arginine, whereas ornithine increases, indicative of high arginase activity. More recently, inhibition of arginase in LPS-treated rodent macrophages was shown to result in enhanced conversion of arginine into citrulline, indicating that arginase and iNOS can compete for arginine [227,228].…”
Section: Arginase and No Synthesismentioning
confidence: 99%
“…Earlier work from several laboratories [222][223][224][225]253,254] led to the notion that macrophage-derived arginase activity at the site of wounds plays a role in the recovery of host tissues from inflammation and infection, not only by removing arginine as substrate for NO synthesis but also by generating ornithine for the synthesis of proline, which is required for collagen synthesis. Supporting this proposition is the fact that there is an early burst of NO synthesis at the wound site, followed by depletion of arginine and a concomitant rise in the concentrations of ornithine and proline [224,253].…”
Section: Arginase and Proline Synthesismentioning
confidence: 99%
“…The relationship between the NOS and arginase involves not only the use of the same substrate (Hecker et al, 1995;Meyer et al, 1997). In healthy individuals, sufficient arginase activity can limit the use of arginine for the synthesis of NO [Currie et al, 1979;Vodovotz et al, 1994). In many studies, macrophage- induced arginase activity in wounds has shown to be involved in tissue healing and protecting against inflammation and infection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one may encounter normal tissue toxicity. These drawbacks may explain why the development of arginase as an antitumor agent has failed despite its activity seen in vitro [28,29]. Nevertheless, recently pegylated arginase has been shown to have activity in hepatocellular carcinoma both in vitro and in vivo due to lack of OCT expression in certain hepatocellular carcinoma cell lines [30].…”
Section: Introductionmentioning
confidence: 99%